The Performance Evaluating of Thresher Machine Attached to the Tractor - Al-Shamiry, Faisal Mohammed Saif; Nasr Mohammed Ali Yahya (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2020)
This research carried out for the purpose of field performance study of the wheat crop threshing machine locally manufactured. The experiments were carried out in Diq village of directors Jhran province of Dhamar governorate. Under different crop feed rate (10 kg, 15 kg and 20 kg) and different thresher drum speed (1400 rpm and 1600 rpm). The Fiat 640 (64hp, 47.7 kW) Tractor was used to run the thresher machine and evaluate the field performance of the thresher. The results showed that the field capacity of the machine (the crop yield that can be threshed by the machine) was 600 kg / h and 1028.6 kg / h of wheat crop yield at 1400 rpm and 1600 rpm respectively. The results showed that highest threshing and cleaning efficiencies of 95 % at feed rate 10 kg with dram speed 1600 rpm .The highest grain loss and grain damage percentage of 0.21 and 0.13 % at drum speed 1600 rpm. The highest grain output 300 kg/h at 20 kg feed rate with 1400 rpm drum speed. The results showed that lowest threshing and cleaning efficiencies of 87 an 84 % respectively at feed rate 20 kg with dram speed 1400 rpm .The lowest grain loss and grain damage percentage of 0.03 and 0.05 % respectively at drum speed 1400 rpm. The highest grain output 300 kg/h at 20 kg feed rate with 1400 rpm drum speed. The lowest grain output 144 kg/h at 10 kg feed rate with 1600 rpm drum speed. The wheat thresher is therefore, a suitable machine with high efficiency and low grain damage and loss percentage for small-scale post-harvest operation.